2002
DOI: 10.1046/j.1525-1594.2002.07066.x
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and End‐Stage Renal Disease in the Developing World

Abstract: In developing countries, multiple comorbidities such as malnutrition, parasitoses, and hemoglobinopathies contribute to the aggravation of anemia observed in patients with end-stage renal diseases. We analyze here the results of a retrospective evaluation of red-cells indices and iron parameters conducted at the end of December 2000 in 304 prevalent Tunisian patients (sex ratio, 1.05; mean age, 53.7 years) receiving chronic hemodialysis for a median duration of 49.6 months (range, 1.6 to 278). Anemia, observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 15 publications
3
16
1
2
Order By: Relevance
“…The higher prevalence of anemia in our study was within the range of figures reported in similar groups of patients elsewhere 2,3,[13][14][15] . However, the predominantly microcytic and hypochromic patterns could be explained either by the inflammatory state associated with chronic infection or by the presence of context specific factors (not investigated) such as nutritional deficiencies, hemoglobinopathies and parasitic diseases 7,8 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The higher prevalence of anemia in our study was within the range of figures reported in similar groups of patients elsewhere 2,3,[13][14][15] . However, the predominantly microcytic and hypochromic patterns could be explained either by the inflammatory state associated with chronic infection or by the presence of context specific factors (not investigated) such as nutritional deficiencies, hemoglobinopathies and parasitic diseases 7,8 .…”
Section: Discussionsupporting
confidence: 90%
“…Our study also has some strengths in the sense that it provides a unique picture, which, in this setting can potentially contribute to raise more attention on anemia, a leading condition in people with CKD. It revealed the positive correlation between hematological profile and erythropoietin and IV iron therapy in a few patients receiving these therapies, even in non-optimal dose, due to financial constraints as reported in similar setting 14,15 . Our efforts in tracking a large number of our participants during follow-up provides some indicators of the burden of anemia in chronic hemodialysis patients and the outcome of anemia correction approaches in the context of limited access to ESA and intravenous iron therapies.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The main limitation of EPO use in developing countries is cost, making it unavailable to most patients [1, 2]. Androgens which are relatively cheap were used in the treatment of anaemia in dialysis patients before the advent of EPO [3].…”
Section: Introductionmentioning
confidence: 99%